Divergent Cesàro Means of Jacobi-Sobolev Expansions - Fejzullahu, Bujar Xh. (Revista Matemática Complutense, 2008)
Let µ be the Jacobi measure supported on the interval [1; 1]. Let introduce the Sobolev-type inner product …. In this paper we prove that, for certain indices δ, there are functions whose Ces_aro means of order δ in the Fourier expansion in terms of the orthonormal polynomials associated with the above Sobolev inner product are divergent almost everywhere on [-1; 1].